Domus Quieta. Facultas Certa: Dialoghi all’italiana nel Palacete Lambertini - Tavares, Ana Ester; Barreira, Hugo (Studi e ricerche di storia dell'architettura, 2025)
This paper examines the impact of Venetian architect Nicola Bigaglia (1841–1908) on Portuguese architecture, with particular emphasis on his celebrated Palacete Lambertini project. Invited to Portugal in 1880 to support the modernization of industrial education, Bigaglia made significant contributions to architecture and the decorative arts, fostering the adoption of Art Nouveau in Portugal. His projects, notably on Lisbon’s Avenida da Liberdade, incorporate Italian architectural elements blended with Portuguese sensibilities, as seen in his award-winning works such as Palácio Lima Mayer and Palacete Lambertini. Focusing on the Palacete Lambertini, a residence commissioned by the Italian-Portuguese musician Michel’angelo Lambertini, this article explores Bigaglia’s use of classical elements — including Serlian arches and culturally resonant inscriptions — to interpret how Italian architectural forms were adapted to express new meanings within the Portuguese context. Through detailed analysis of this mansion alongside comparisons with contemporary architectural trends, this study sheds light on the interplay between Bigaglia’s Italian heritage and his Portuguese surroundings, underscoring processes of cultural adaptation and the dialogue between designer and client identities. Marking the 120th anniversary of the Palacete Lambertini, this paper deepens our understanding of Italian architectural influence in Portugal and its evolving cultural significance.